Leadership Principal Instruction in Implementation Independent Curriculum in Schools Upper Intermediate - Sungkalang, Agustinus; Wicaksono, Luhur; Ulfah, Maria (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to analyze and find out the principal's instructional leadership in implementing the independent curriculum, especially at Santo Fransiskus Assisi Pontianak High School, North Pontianak District, West Kalimantan Province. This form of research uses a qualitative approach with a case study type of research. There were four research subjects, namely, the principal, deputy principal for curriculum, deputy principal for student affairs, and teachers. The data collection method is carried out using techniques interviews , observations , and documentation . Data analysis uses data reduction , data presentation and withdrawal conclusion / verification . The results of this research show that the principal has carry out leadership teaching well and effectively so that in communicating vision and mission school as well as apply ikm carried out according to objectives . As for leadership strategies instruction carried out by the school principal namely , (1) give exemplary , (2) dialogue with teachers, (3) effective communication , (4) facilitating teachers, (5) supervising effective . Important steps have been taken taken show that the principal own commitment and focus on achievement implementation of SMEs. By applying leadership instructional show work climate created at St Francis High School Assisi Pontianak is running effective , conducive , and running optimally.